On intuitionistic L-fuzzy bi-ideals of semigroups. (4th July 2019) - Sumathi, R.; Sathappan, K.E.
Abstract: In this paper, we introduce the concept of intuitionistic L-fuzzy bi-ideals in semigroups and investigate some of their related properties. Also we introduce intuitionistic L-fuzzy (1, 2) ideal in semigroup and obtain certain characterizations.